2020
DOI: 10.1002/2211-5463.12795
|View full text |Cite
|
Sign up to set email alerts
|

WWP1 knockout in mice exacerbates obesity‐related phenotypes in white adipose tissue but improves whole‐body glucose metabolism

Abstract: White adipose tissue (WAT) is important for maintenance of homeostasis, because it stores energy and secretes adipokines. The WAT of obese people demonstrates mitochondrial dysfunction, accompanied by oxidative stress, which leads to insulin resistance. WW domain‐containing E3 ubiquitin protein ligase 1 (WWP1) is a member of the HECT‐type E3 family of ubiquitin ligases and is associated with several diseases. Recently, we demonstrated that WWP1 is induced specifically in the WAT of obese mice, where it protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Wwp1 is a HECT family ligase whose activity has been studied with regard to cancer, where its increased activity is correlated with aggressive tumors ( Chen et al, 2007 ). Knockout mice have short tibias (Mouse Genome Informatics and the International Mouse Phenotyping Consortium) and are obese ( Hoshino et al, 2020 ), two phenotypes that are commonly seen in cilia-defective mice. Wwp1 is reported to catalyze monoubiquitination and the extension of a poly-Ub chain through the rapid addition of two to four K63-linked subunits followed by slower addition of a variety of linkages onto the initial short K63 chain ( French et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wwp1 is a HECT family ligase whose activity has been studied with regard to cancer, where its increased activity is correlated with aggressive tumors ( Chen et al, 2007 ). Knockout mice have short tibias (Mouse Genome Informatics and the International Mouse Phenotyping Consortium) and are obese ( Hoshino et al, 2020 ), two phenotypes that are commonly seen in cilia-defective mice. Wwp1 is reported to catalyze monoubiquitination and the extension of a poly-Ub chain through the rapid addition of two to four K63-linked subunits followed by slower addition of a variety of linkages onto the initial short K63 chain ( French et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…GO term and pathway enrichment analysis showed that DEGs were highly enriched in the present investigation, which undoubtedly verifies the reliability of our results. Signaling pathways include cytokine signaling in immune system [ [87], CES1 [88], CYP19A1 [89], PLAC8 [90], CD36 [91], GIPR (gastric inhibitory polypeptide receptor) [92], ARG1 [93], MSR1 [94], DOCK2 [95], S1PR1 [96], OXTR (oxytocin receptor) [97], F11R [98], LEPR (leptin receptor) [99], AR (androgen receptor) [100], DKK3 [101], FOXO1 [102], PIK3CB [103], WWP1 [104], PHIP (pleckstrin homology domain interacting protein) [105], MPZL3 [106], FBXO2 [107], GUCY2C [108], ADRA2A [109], CHRNA5 [110], GLP2R [111], SDC3 [112], NFAT5 [113], PON2 [114], PRNP (prion protein) [115], DGKE (diacylglycerol kinase epsilon) [116], ARHGAP21 [117], COQ2 [118], EPHX2 [119] and FAM3C [120] were observed to be associated with the progression of obesity. Vargas-Alarcón et al [121], Frantz et al [122], Bosè et al [123], Gu et al [124], Liu et al [125], Szirák et al [126], Ye et al [127], Alikhah et al [128], Chen et al [129], Mao et al…”
Section: Discussionmentioning
confidence: 99%
“…WWP1 is a 922 amino acid protein that contains one C2 domain, four WW domains and one HECT domain (Zhi and Chen, 2012). The C2 domain determines the subcellular localization of the molecule, while the WW domain binds to the proline-rich sequence (PY motif) of the substrate protein (Hoshino et al, 2020). Studies have shown that WWP1 regulates a variety of cellular biological processes such as protein transport and degradation, signal transduction and transcription (Jia et al, 2021).…”
Section: Wwp1 Wwp1 Functionmentioning
confidence: 99%